Evaluating Environmental Management Accounting of Community-driven Material Recovery Facility (CdRMF) - Istigfarin, Wilda Auwalina; Prastiwi, Arum; Shahbudin, Amirul Shah Md; Adib, Noval (Universitas Diponegoro, 2026)
Environmental management accounting (EMA) has gained attention; however, its use in grassroots waste management remains limited, especially in communities with scarce resources. This study explores how community-driven material recovery facilities (CdMRFs), or known as waste banks, Mitra Kita in Blitar, Indonesia, apply EMA principles in their daily operations. The focus is on how local groups adapt accounting practices to maintain accountability, transparency, and sustainability, despite financial and operational constraints. A qualitative case study was conducted through interviews, observations, and document analysis, supported by triangulation and member validation. The findings show that the CdMRF develops practical financial routines for recording expenses, calculating unit costs, and preparing semiannual reports, which strengthen transparency and trust among members. Community participation plays a central role, as routine activities generate financial, social, and ecological value. However, long-term sustainability is challenged by limited managerial skills, dependence on key leaders, and fluctuating waste prices. This study expands EMA discussions by shifting attention from formal institutions to community initiatives in developing contexts. It demonstrates that simplifying accounting can make environmental management more grounded and adaptable. The findings offer guidance for policymakers seeking to strengthen CdMRFs and similar programs within broader circular economy and sustainability efforts.